The Role of Digital Learning Media in Enhancing Elementary School Students' Speaking Skills - Jamal, Ahmad Faozan; Riyanti, Dessy Az-Zahra Putri; Azizah, Farah Nur; Chamdani, Muhammad (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Speaking skills are essential competencies that students need to develop. This study aims to observe the effectiveness of digital media in enhancing elementary school students' speaking abilities while also exploring its advantages and disadvantages. The research involved a limited review of 10 national journal articles published within the last seven years. The findings indicate that various forms of digital media—such as voice notes (WhatsApp), digital comics, pop-up books, Articulate Storyline, multimedia, digital posters, Duolingo animations, Wordwall, and digital storytelling—are effective in improving students' speaking skills. These media are easy for students to use and understand. With strong speaking skills, students are better able to express ideas, opinions, and feelings; engage in meaningful interactions with peers and others; participate actively in the learning process; and build a deeper understanding of academic subjects. Therefore, digital media are appropriate tools for students, as they significantly contribute to the development of speaking skills. AbstrakKeterampilan berbicara merupakan suatu keterampilan penting yang perlu diperhatikan oleh para siswa.Tujuan penelitian ini untuk mengamati efektivitas penggunaan media digital yang berperan penting dalam peningkatan keterampilan berbicara siswa sekolah dasar serta menggali kelebihan dan kekurangan media digital. Hasil penelitian menunjukkan bahwa Peneliti melakukan pengkajian terbatas pada 10 artikel jurnal nasional dalam rentang 7 tahun terakhir. Berdasarkan sumber kajian diperoleh media digital berikut seperti: media digital voice note (WhatsApp),komik digital, pop up book, Articulate Storyline, multimedia, poster digital, animasi Duolingo, Wordwall, dan digital storytelling efektif dalam meningkatkan keterampilan berbicara siswa, karena mudah digunakan dan dipahami oleh siswa. Berbekal dengan keterampilan berbicara yang baik, para siswa dapat mengungkapkan gagasan, pendapat dan perasaan untuk berinteraksi dengan teman sejawat atau orang lain, ikut berpartisipasi aktif dalam pembelajaran, serta membangun pemahaman yang lebih mendalam terhadap mata pelajaran. Oleh karena itu, media digital merupakan media yang tepat untuk digunakan oleh para siswa karena berpengaruh besar terhadap peningkatan kemampuan mereka terutama pada keterampilan berbicara.